Development of Interactive Multimedia Based on the Pancasila Student Profile for Pancasila Education in Fourth Grade Elementary School - Ni Luh Puspa Cantika Dewi; Ni Ketut Suarni; Dewi Anzelina (Jurnal Pendidikan Multikultural Indonesia, 2025)
Pancasila Education in elementary schools continues to face significant challenges, particularly the low level of student engagement caused by the limited use of innovative and interactive learning media. Conventional instructional approaches often fail to stimulate active participation and deep conceptual understanding among students. This study aimed to analyze, develop, and evaluate interactive multimedia based on the Pancasila Student Profile, as well as to examine its validity, quality, and effectiveness in improving students’ understanding and engagement. This research employed a Research and Development (R&D) design using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The study involved 13 fourth-grade elementary students. Data were collected using expert validation sheets, closed-ended questionnaires, and learning achievement tests. The instruments were validated by content, instructional design, and media experts. Data were analyzed using descriptive quantitative and qualitative techniques, along with inferential statistical analysis through a dependent t-test. The findings indicated that the multimedia achieved very high validity scores from experts and significantly improved students’ learning outcomes, as demonstrated by the t-test results showing a statistically significant increase. These results suggest that interactive multimedia based on the Pancasila Student Profile effectively enhances students’ conceptual understanding and learning engagement. The study implies that integrating interactive digital media can support.